Peningkatan kualitas nira sorgum manis (Sorghum bicolor L) dan potensinya sebagai substrat fermentasi asam glutama - Rozalia Rozalia; Mulyorini Rahayuningsih; Mohamad Yani (Agroindustrial Technology, University of Trunojoyo Madura, 2024)
Sweet sorghum is the potential in Indonesia to be used as a fermentation medium for glutamic acid production. The sorghum plant resembles sugar cane which has sap in the stem. Sorghum is a plant with high sugar content and high biomass productivity. The high sugar content in sorghum sap is known from the total dissolved solids. The evaporation process on sorghum juice increases the sugar content and can inactivate microbial activity. Glutamic acid fermentation needs a substrate source derived from sugar for the growth of the producing microbes. Therefore, this study aims to describe the sugar content in sorghum juice before and after the evaporation process so that it can be used as a substrate source for glutamic acid production. This research was carried out using the evaporation method of sorghum juice for 15 minutes at a temperature of 85 - 100 oC, so a concentrated sorghum sap was obtained. The analysis was pH, total dissolved solids (oBrix) using a refractometer, and reducing sugar content using the DNS method. The results obtained in this study indicated a significant increase in the quality and sugar content of sorghum sap with a pH of 4.81 ± 0.01 to 5.55 ± 0.03, total dissolved solids from 10.44 ± 0.09 to 34.80 ± 0.02 (oBrix), and reduced sugar content from 114.10 ± 0.45 to 271.74 ± 0.26 g/l. The sugar content allows sorghum juice to be used as raw material in industrial microbiology, especially for the production of glutamic acid.